Advantages of Teaching Students Using Multimedia Tools and Site in Teaching Drawing - Dilfuza Islomovna Mamurova (International Journal on Human-Computing Studies, 2022)
The effectiveness of lessons can be increased by using multimedia tools in the learning process. Lessons with multimedia tools increase the student's interest in the lesson and the level of knowledge. Information technology also means the Internet and the basics of its use. The Internet is a global computer network that connects thousands of local and regional computer networks. The Internet is a complex system of self-formation and self-management.